MODES OF RELATING TO MUSIC - Campos, Luís Melo (2011)
The concept of modes of relating to music is presented, consisting of three conceptual levels and organized into thirteen analytical dimensions that may be operationalized for the purposes of observing empirical situations. It involves closely examining a diversified set of relationships specific to musical practices, in an integrated manner, qualitatively typifying the forms of enjoying them around two poles: the essential and the relational. Although formulated to analyze professional musicians, it is maintained that the concept is also suitable (with adaptations) for the analysis of musical consumptions and other spheres of cultural production (intellectual and artistic).